Social Delta Formation : A Grounded Theory Approach to Afro-Latin American Cityscapes - Gruber, Valerie (2024)
Afro-Latin American lifeworlds are shaped by persistent processes of de- and reterritorialization. Theorizing on these dynamics sheds light on underlying forces of exclusion and discrimination that need to be understood in order to overcome them. This paper presents the results of a grounded theory building process carried out in Salvador da Bahia (Brazil) and Cartagena de Indias (Colombia) throughout six years. Comparing these former ports of the transatlantic trade in enslaved Africans, I propose a socio-moral cartography that illustrates the tacit dimension of Afrodiasporic (re-)existence. Extensive ethnographic fieldwork, qualitative interviews and participatory action research with artistic groups from Afrodescendant communities allowed scrutinizing the traumatic structures that lie behind both cityscapes. As a result, I present a theory of social delta formation that draws on the conceptual analogy of a river mouth extending into the sea, grounded on the fact that the communities involved in the co-creation of knowledges historically built their neighborhoods by territorializing parts of the Atlantic shore with debris. This socio-moral cartography depicts opportunities for social transformation as well as restrictions due to racist exclusion, disclosing ethics and aesthetics that permeate daily life in (post)colonial and (post)enslavement cityscapes. The theory of social delta formation is applicable both in academic and community settings, as it highlights the broader social, moral and territorial impact of the coloniality of power. It can be extrapolated to many contexts where Afrodescendant people are structurally marginalized and displaced, reinventing their existence every day.
Keywords: Socio-moral cartography; African diaspora; coloniality; Brazil; Colombia